1982
DOI: 10.1056/nejm198212233072601
|View full text |Cite
|
Sign up to set email alerts
|

The Cutaneous Infiltrates of Leprosy

Abstract: We report on the characteristics of cells in the cutaneous lesions and blood of 21 patients with lepromatous, tuberculoid, and intermediate forms of leprosy. A large proportion of the infiltrates in lepromatous lesions consist of macrophages heavily parasitized with Mycobacterium leprae. The T cells in the lesions are devoid of OKT4/Leu 3a-positive ("helper") cells and consist almost exclusively of OKT8/Leu 2a-positive ("suppressor") populations. In contrast, the tuberculoid infiltrates contain well-organized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…The study group included 25 lepromatous (LL) (see diagnosis below), 10 borderline lepromatous (BL), and 55 tuberculoid (BT and TT) patients and 50 non-leprosy control individuals. Sex and age distribution were as follows: BL and LL patients, 3 (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study group included 25 lepromatous (LL) (see diagnosis below), 10 borderline lepromatous (BL), and 55 tuberculoid (BT and TT) patients and 50 non-leprosy control individuals. Sex and age distribution were as follows: BL and LL patients, 3 (7).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, tuberculoid leprosy lesions exhibit large numbers of lymphocytes, granuloma formation, and the absence of appreciable numbers of intracellular bacteria (1,2). Monoclonal antibodies to human leukocytes and their subsets have been used to determine the phenotype of the cells in dermal infiltrates (3)(4)(5)(6). These studies showed that in lepromatous lesions there is not only a marked reduction in the numbers of T cells (compared to tuberculoid lesions) but also a selective absence of T lymphocytes of the OKT4+ subset.…”
mentioning
confidence: 99%
“…Immunohistological studies using monoclonal antibodies to characterize T-lymphocyte subsets in granulomas revealed striking differences in the various types of leprosy (2,3). Tuberculoid (TT and BT) lesions contain a predominance of T cells of the CD4+ helper/inducer subset, whereas lepromatous lesions contain mainly T cells of the CD8+ suppressor/cytotoxic subset in proportions quite distinct from the normal peripheral blood CD4+/CD8+ ratio (4).…”
mentioning
confidence: 99%
“…1). In association with this defect, helper T cells fail to migrate and to accumulate in the dermal lesions, and adequate amounts of lymphokines are not synthesized and released locally (2,3). This absence of local lymphokines leads to a failure of macrophage activation, and these cells serve as permissive hosts for the bacilli (4).…”
mentioning
confidence: 99%